PERAN KOMISI PEMILIHAN UMUM (KPU) KOTA SURAKARTA DALAM MENINGKATKAN JUMLAH PEMILIH MUDA PADA PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024 - Rahayu, Vina Dwi; Suhita, Damayanti (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
The General Election Commission (KPU) of Surakarta City plays a strategic role in organizing the 2024 election, particularly in increasing the participation of young voters, who constitute the largest group of eligible voters compared to other demographic groups. In the 2019 election, the voter participation rate in Surakarta City was only 75%, lower than the national average of 80%. However, thanks to various efforts by the KPU, voter participation significantly increased to 87% in the 2024 election. This study aims to analyze the role of KPU Surakarta in increasing young voter participation using Biddle and Thomas’ role theory, which includes four key indicators: expectation, norms, performance, and evaluation. To raise awareness and engagement among young voters, KPU Surakarta implemented various strategies, such as social media outreach, political education programs for first-time voters, and collaboration with youth organizations. Social media platforms, particularly Instagram, Twitter, and TikTok, were utilized to disseminate election-related information in a more engaging and accessible manner for younger generations. Additionally, programs like “KPU Goes to Campus” and “KPU Goes to School” were conducted to provide a deeper understanding of the importance of voting rights and the role of young voters in democracy. KPU also collaborated with youth organizations, such as OSIS (Student Council) and Badan Eksekutif Mahasiswa (BEM – Student Executive Board), to reach more young people in political education activities. The study findings indicate that a more innovative and technology-based approach has successfully increased young voter engagement. Although challenges remain, such as political apathy and low political literacy among young people, KPU’s strategies for increasing youth voter participation have proven effective. The 16% increase in voter participation from the 2019 to the 2024 electionreflects KPU’s success in attracting young voters through modern methods tailored to the characteristics of the current generation. Therefore, KPU must continue to develop more innovative strategies, simplify election information, and enhance youth involvement in the democratic process. Keyword : Election, young votes, Surakarta City Election Commission, Participation